Core competency requirements among extension workers in Peninsular Malaysia: use of Borich’s needs assessment model - Umar, Sulaiman; Man, Norsida; Mohd Nawi, Nolila; Abd. Latif, Ismail; Abu Samah, Bahaman (Elsevier, 2017)
The study described the perceived importance of, and proficiency in core agricultural extension competencies among extension workers in Peninsular Malaysia; and evaluating the resultant deficits in the competencies. The Borich's Needs Assessment Model was used to achieve the objectives of the study. A sample of 298 respondents was randomly selected and interviewed using a pre-tested structured questionnaire. Thirty-three core competency items were assessed. Instrument validity and reliability were ensured. The cross-sectional data obtained was analysed using SPSS for descriptive statistics including mean weighted discrepancy score (MWDS). Results of the study showed that on a scale of 5, the most important core extension competency items according to respondents' perception were: "Making good use of information and communication technologies/access and use of web-based resources" (M=4.86, SD=0.23); "Conducting needs assessments" (M=4.84, SD=0.16); "organizing extension campaigns" (M=4.82, SD=0.47) and "Managing groups and teamwork" (M=4.81, SD=0.76). In terms of proficiency, the highest competency identified by the respondents was "Conducting farm and home visits (M=3.62, SD=0.82) followed by 'conducting meetings effectively' (M=3.19, SD=0.72); "Conducting focus group discussions" (M=3.16, SD=0.32) and "conducting community forums" (M=3.13, SD=0.64). The discrepancies implying competency deficits were widest in "Acquiring and allocating resources" (MWDS=12.67); use of information and communication technologies (ICTs) and web-based resources in agricultural extension (MWDS=12.59); and report writing and sharing the results and impacts (MWDS=11.92). It is recommended that any intervention aimed at developing the capacity of extension workers in Peninsular Malaysia should prioritize these core competency items in accordance with the deficits established in this study.